PENGARUH PERSEPSI HARGA DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA PADA LOYALIAS PELANGGAN (Studi Pada Distributor Centrarium Di Semarang) (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this research is to find out and analyze whether or not there is a relationship between the perception of price, product quality, customer satisfaction, customer loyalty in the Distributor Centrarium Semarang. The population was taken to this research is the customer agents and retailers centrarium that add up to 80 people. Samples were taken using the methods of descriptive research is the questionnaire. The data collected is processed further using multiple regression analysis techniques with the help of the software SPSS (Statistical Package for Social Science). The results of the analysis showed. 1. The perception of a positive and influential prices significantly to customer satisfaction. 2. Product quality and insignificant negative effect towards customer satisfaction. 3. Product quality and insignificant negative effect towards customer satisfaction. 4. positive effect customer satisfaction and significantly to customer loyalty. 5. positive effect customer satisfaction and significantly to customer loyalty. .Keywords: Perception of price, product quality, customer satisfaction, and customer loyalty.